BOOK REVIEW: Hrvoje Baričević, Danijela Marjanić (coords.), “Prvi Svjetski Rat. Vodič kroz fondove i zbirke Hrvatskoga državnog arhiva” [“The First World War. The guidebook of funds and collections from the State Archive of Croatia, Zagreb”], Zagreb, Hrvatski državni arhiv, 2016, 830 p., ISBN: 9789537659424 - KATANIĆ, Filip (Studia Universitatis Babeș-Bolyai Historia, 2018)
This book is one of the most recent editorial publications under the aegis of the Croatian State Archives in Zagreb, in the series of publications commemorating the centennial of the First World War. It is also the first comprehensive archive guidebook on funds and collections across Croatia that contains First World War material and the period that follows. The volume, written in Croatian but with a summary in English, is the product of the collective effort of a large number of scholars, of which we can name Filip Hameršak and Vida Pavliček. Recently, the book also entered the collections of the “Lucian Blaga” Central University Library in Cluj-Napoca (The Library of Modern History), which is why we bibliographically signal its presence. Although the book and most of the archival material are in Croatian, we considered that the work deserves to be presented, both as a methodological model as well as because of the fact that some of the archive information that is contains can be related to the history of Romania as part of Austro-Hungary history and as a state that took part in the First World War, and it may also be of interest for the Romanian historians.